Exploration of Socio-Scientific Issues through Coffee Brewing Methods to Explore Physics Literacy : Place Based Education at SK Coffee Lab Kediri - Silvi Aviandari; Nadi Suprapto; Beken Arymbekov (Indonesia Approach Education, 2022)
The taste of coffee is not only influenced by the type of coffee but also by the brewing methods. The phenomenon of brewing coffee is an interesting scientific phenomenon that can be used as a Socio-scientific Issues (SSI) theme. SSI are social issues that exist in society, contain the basis of science, and in their resolution trigger dialogue, discussion and debate. The purpose of this study is to determine the level of science literacy as an impact of SSI exploration on the phenomenon of coffee brewing methods. This research uses qualitative methods and is conducted at SK Coffee Lab Kediri with baristas as the source of information. Interviews are arranged based on indicators of science literacy with four main components, knowledge of science, the investigation nature of science, science as a way of thinking, and the interaction of science, technology, and society. Based on this research, the results were obtained that baristas at SK Coffee Lab have a sufficient level of physics science literacy with a percentage of 70%. While the descriptions of each indicator are as follows: the indicator of knowledge of science scored 75% with good criteria, the indicator of the investigation nature of science scored 75% with good criteria, on the indicator of science as a way of thinking scored 80% with good criteria and on indicators of the interaction of science, technology and society scored 80% with good criteria.